Anterior spinal hardware erosion of the pharyngoesophagus: A difficult reconstructive challenge—Our experience in nine patients. (30th December 2022) - Peddireddy, Nithin S.; Yalamanchi, Pratyusha; Kashlan, Osama; Park, Paul; Reddy, Rishindra M.; Chinn, Steven B.; Casper, Keith A.; Malloy, Kelly M.; Stucken, Chaz L.; Prince, Mark E. P.; Rosko, Andrew J.; Spector, Matthew E.
Key Points: Pharyngoesophageal perforation secondary to anterior spinal hardware erosion is a difficult dilemma with many reconstructive options available. Multidisciplinary approach with thoracic surgery and neurosurgery is critical and can lead to excellent post‐operative swallowing outcomes. Patients who have a history of radiation to the head and neck benefit from the use of tissue flaps. Culture‐directed antibiotic use is important to ensure surgical healing and given the risk of salivary fistula. After reconstruction, there may be need for further, less invasive interventions such as diverticulectomy or oesophageal dilation.